In vitro and in vivo phosphorylation of the Ca(v)2.3 voltage-gated R-type calcium channel - Schneider, T. (Channels (Austin), 2018)
During the recording of whole cell currents from stably transfected HEK-293 cells, the decline of currents carried by the recombinant human Cav2.3+β3 channel subunits is related to adenosine triphosphate (ATP) depletion after rupture of the cells. It reduces the number of functional channels and leads to a progressive shift of voltage-dependent gating to more negative potentials (Neumaier F., et al., 2018). Both effects can be counteracted by hydrolysable ATP, whose protective action is almost completely prevented by inhibition of serine/threonine but not tyrosine or lipid kinases. These findings indicate that ATP promotes phosphorylation of either the channel or an associated protein, whereas dephosphorylation during cell dialysis results in run-down. Protein phosphorylation is required for Ca(v)2.3 channel function and could directly influence the normal features of current carried by these channels. Therefore, results from in vitro and in vivo phosphorylation of Ca(v)2.3 are summarized to come closer to a functional analysis of structural variations in Ca(v)2.3 splice variants.